2020
DOI: 10.3390/rs12020341
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Type Forest Change Detection Using BFAST and Monthly Landsat Time Series for Monitoring Spatiotemporal Dynamics of Forests in Subtropical Wetland

Abstract: Land cover changes, especially excessive economic forest plantations, have significantly threatened the ecological security of West Dongting Lake wetland in China. This work aimed to investigate the spatiotemporal dynamics of forests in the West Dongting Lake region from 2000 to 2018 using a reconstructed monthly Landsat NDVI time series. The multi-type forest changes, including conversion from forest to another land cover category, conversion from another land cover category to forest, and conversion from for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…The map of Figure 7(a) was reclassified to represent two classes, "change" and "no-change" (Figure 8). The accuracy assessment estimates an overall accuracy of 0.85±0.02 at the 95% confidence level, which is similar to some previous research 3 . Omission and commission errors of class "change" are 0.30±0.02 and 0.19±0.02.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The map of Figure 7(a) was reclassified to represent two classes, "change" and "no-change" (Figure 8). The accuracy assessment estimates an overall accuracy of 0.85±0.02 at the 95% confidence level, which is similar to some previous research 3 . Omission and commission errors of class "change" are 0.30±0.02 and 0.19±0.02.…”
Section: Resultssupporting
confidence: 88%
“…This paper describes results obtained with Landsat 8 time series and Breaks For Additive Season and Trend (BFAST) 1 in a region of central Portugal. BFAST has been used to analyze Normalized Difference Vegetation Index (NDVI) time series and other vegetation indices to detect deforestation in a range of biomes 2,3 , but rarely in Mediterranean and Atlantic biomes (but see 4 ). BFAST decomposes a time series into trend and seasonal components with methods for detecting abrupt changes within the two components.…”
Section: Introductionmentioning
confidence: 99%
“…With remote sensing, deforestation monitoring systems use a bunch of automatic methods, based on the change detection techniques [12,21,26] e.g. time-series analysis of vegetation indices [38], image preprocessing to detect changes between a pair of images [49], machine learning classification [24,57]. But recently, the deep learning has demonstrated great potential in remote sensing, due to its ability to extract features from the spectral-spatial-temporal image data [40], providing state-of-the-art results in remote sensing change detection.…”
Section: Introductionmentioning
confidence: 99%
“…Higher NDVI values suggest higher amounts of photosynthetic active biomass. As the most popular index, NDVI time series have been used in many forest disturbance detection and monitoring efforts [38,39].…”
Section: Landsat-derived Spectral Indicesmentioning
confidence: 99%
“…However, the high accuracies presented by NDVI is somewhat surprising given the fact that studies showed low accuracies related to this index in tropical forests [13,47]. This is a particularly useful result indicating why NDVI is still the most frequently used index in remote sensing, and has been presented in forest disturbances detection and monitoring [38,39].…”
Section: Vegetation Sensitivity To Spectral Indicesmentioning
confidence: 99%